Effect of continuous oral suctioning on the development of ventilator-associated pneumonia: A pilot randomized controlled trial. - Chow, Meyrick C.M.; Kwok, Shu-Man; Luk, Hing-Wah; Law, Jenny W.H.; Leung, Bartholomew P.K. (International Journal of Nursing Studies, 2012)
Abstract: Background: Both continuous and intermittent aspiration of subglottic secretions by means of specially designed endotracheal tubes containing a separate dorsal lumen that opens into the subglottic region have been shown to be useful in reducing ventilator-associated pneumonia (VAP). However, the high cost of these tubes restricts their use. Objective: The aim of this pilot randomized controlled trial was to test the effect of a low-cost device (saliva ejector) for continuous oral suctioning (COS) on the incidence of VAP in patients receiving mechanical ventilation. Methods: The study was conducted in the six-bed medical-surgical ICU of a hospital with over 400 beds that provides comprehensive medical services to the public. The design of this study was a parallel-group randomized controlled trial. While both the experimental and control groups used the conventional endotracheal tube, the saliva ejector was only applied to patients assigned to the experimental group. The device was put between the patient''s cheek and teeth, and then connected to 100mmHg of suction for the continuous drainage of saliva. Results: Fourteen patients were randomized to receive COS and 13 patients were randomized to the control group. The two groups were similar in demographics, reasons for intubation, co-morbidity, and risk factors for acquiring VAP. VAP was found in 3 patients (23.1%; 71 episodes of VAP per 1000 ventilation days) receiving COS and in 10 patients (83.3%; 141 episodes of VAP per 1000 ventilation days) in the control group (relative risk, 0.28; 95% confidence interval, 0.10–0.77; p =0.003). The duration of mechanical ventilation in the experimental group was 3.2 days (SD 1.3), while that in the control group was 5.9 days (SD 2.8) (p =0.009); and the length of ICU stay was 4.8 days (SD 1.6) versus 9.8 days (SD 6.3) for the experimental and control groups, respectively (p =0.019). Conclusion: Continuous clearance of oral secretion by the saliva ejector may have an important role to play in reducing the rate of VAP, decreasing the duration of mechanical ventilation, and shortening the length of stay of patients in the ICU.